Pendidikan Anti Korupsi dalam Pembentukan Karakter Mahasiswa - Muhamad Yusar (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
In a globalized era of change and ethical and political complexity, the role of education in shaping individual character and guiding social and political development is becoming increasingly important. Society's struggle to prevent and address corruption is a fundamental measure of prosperity and sustainable development. Corruption, as an act that undermines the integrity of social and political systems, is a serious issue that involves all levels of society. Therefore, early education on corruption prevention has great potential to play a key role. Anti-corruption education is a widely accepted approach in the fight against corruption. In addition to understanding the concept of corruption, it emphasizes the formation of strong character and ethical values to guide individuals in making decisions with integrity throughout their lives. In the higher education environment, the role of anti-corruption education is increasingly important as students are the future leaders who will shape the direction of society's development. This study highlights the importance of anti-corruption education in shaping student character. The results show that anti-corruption education contributes positively to students' integrity, ethical awareness, and anti-corruption attitudes. Anti-corruption education has brought a positive impact in shaping the character of students, continuous efforts are needed to strengthen this program and ensure a cleaner, more integrity, and active young generation in preventing corruption in the future.